PENGARUH LATIHPengaruh Latihan Fisik Terhadap Kemampuan Kognitif Lansia Di Desa Ngesrep Kecamatan Ngemplak Kabupaten BoyolaliAN FISIK TERHADAP KEMAMPUAN KOGNITIF LANSIA DI DESA NGESREP KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Andreany Kusumowardani; Endang Sri Wahyuni (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract : Exercise, Older People, Cognitive Performance, MMSE. Cognitive performance in older people declines gradually due to aging process. It raises problems in functional daily activities, risks of injury, and dependency. Literatures have been revealed the benefits of exercise for health, not only physically, but also mentally. The purpose of this study was to determine the effect of exercise on the cognitive performance of older people in Ngesrep Village, Boyolali District. This study was a quasi experimental one group pre test- post test with control group. A constitutive sampling method was applied to get subjects, and found 20 people for each experiment and control group. The instrument used was Mini Mental State Examination (MMSE). Based on paired t-test analysis in the experiment group, it was found a significant difference on the cognitive performance pre and post exercise intervention (α = 0.05, t = 2.492, p = 0.022, r = 0.657). In the control group, there was no diferrence in pre and post test (p = 0.053). Based on independent t-test analysis between experiment and control group, it was found a significant difference before the intervention (p = 0.031), but after the intervention, there was no difference between the two groups. It was due to the increasing MMSE’s score on the experiment group, whereas the score of control group was relatively the same. Physical exercise had a significant influence on the cognitive performance of older people in this study, so it should be held in Ngesrep Village’s Posyandu routinely.